(3GdeHOY TQM GdebfY dehab GdOjf Hf bOGeI GdebOSis - (3HQgGf GdOjf CHh ESMGb EHQGgje Hf eadM GdebOSi GdMfHdis; (3CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3BNQgG (B:s
(3BNQ HGH YbO GdReI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3Gdabg GdMfHdjs